Effect of marketing mix and service quality on customer satisfaction and loyalty (A study on PT. Mutiara Cemerlang Utama Bali) - Ni Nyoman Ardani (Unit Publikasi Ilmiah, P3M, Politeknik Negeri Bali, 2021)
The COVID – 19 pandemic been made bad impact all tourism sector. Travels agents need to be adapted to pandemic condition to survive in this current situation. The purpose of this research is to test the influence of marketing mix, quality of service on customer satisfaction and loyalty. This study took samples on the research population customers of PT. Mutiara Cemerlang Utama Bali who buys domestic and international flight tickets, makes hotel room reservations, tour package, India pilgrimage tours, assistant to make passport and visa extension. This research leads to descriptive and verificative research called explanatory research. The data was collected by interviewing and disseminating questionnaires by purposive sampling method processed using Partial Least Square (PLS) analysis tool, the number of samples used by 120 samples. The results obtained in this study are that the marketing mix has a significant positive effect on customer satisfaction, the quality of service has a significant positive effect on customer satisfaction, but marketing mix and quality of service have a positive effect on customer loyalty. This is due to several factors that affect such as the price competition of travel agents. Customer satisfaction has a positive and significant effect on customer loyalty.